The impact of faith-based narratives on climate change adaptation in narikoso, fiji - Bertana, Amanda (Anthropological Forum, 2020)
Most research on climate change in South Pacific island communities has privileged people’s observations of physical environmental change with less attention paid to how people interpret the causes of these changes. Increasingly, more studies are focusing on how communities are receiving messages about environmental degradation, and from whom they are receiving them. This case study draws upon ethnographic research conducted in November 2015 in Narikoso on Ono Island in Fiji’s Kadavu Group. This village was in the process of relocating inland as a response to shoreline erosion and severe coastal flooding. By employing data drawn from interviews with government actors, religious leaders, and residents of Narikoso village along with fieldnotes from participant observation, this paper examines how village residents interpreted coastal flooding and shoreline erosion according to the biblical story of Noah’s Ark alongside a secular narrative of climate change. I conclude by showing the unique challenges these worldviews had on the community’s decision to relocate. © 2020 The University of Western Australia.
8 citations (Crossref) [2023-10-31] tex.ids: bertanaImpactFaithbasedNarratives2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85092596428 type: Article
Keywords: Fiji; Relocation; climate change adaptation; dept.soc; peer-reviewed; religion; sea level rise